Review of literatures on trust factors affecting customer's purchase intention on SOHO seller: S-commerce context - Ramli, R. (International Information Institute Ltd., 2016)
Small home-grown businesses have evolved with the emerging of web 3.0 technology. As the businesses nature based on e-commerce concept but in a smaller scale, SOHO face difficulty to gain customer's trust as they are using Social Network Sites (SNSs) in steering their business online. Trust between seller and customer play important role in conducting business online as goods or services are not tangible. Hence, a study on factors that contribute to trust that lead to customer's purchase decision in SOHO environment are required. Â© 2016 International Information Institute.